2019
DOI: 10.1139/bcb-2017-0310
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation in hematopoiesis: RNA binding proteins take control

Abstract: Normal hematopoiesis is sustained through a carefully orchestrated balance between hematopoietic stem cell (HSC) self-renewal and differentiation. The functional importance of this axis is underscored by the severity of disease phenotypes initiated by abnormal HSC function, including myelodysplastic syndromes and hematopoietic malignancies. Major advances in the understanding of transcriptional regulation of primitive hematopoietic cells have been achieved; however, the post-transcriptional regulatory layer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 127 publications
0
20
0
Order By: Relevance
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA‐binding proteins, then acts as an oncogene or a suppressor oncogene . In this study, we found that knockdown of MAPKAPK5‐AS1 in CRC cells could lead to changes in related downstream genes, including p15 , p21 , p27 , p57 , KLF2 , and Trail .…”
Section: Discussionmentioning
confidence: 64%
“…In this study, we analyzed 2 sources Many lncRNAs can regulate the expression of downstream target genes by forming complexes with RNA-binding proteins, [27][28][29][30] then acts as an oncogene or a suppressor oncogene. [31][32][33][34][35] In this study, we found that knockdown of MAPKAPK5-AS1 in CRC cells could lead to changes in related downstream genes, including p15, p21, p27, p57, KLF2, and Trail. Among them, p21 has high basal expression abundance in CRC cells, which aroused our interest.…”
Section: Discussionmentioning
confidence: 66%
“…Considering the complexity of the RBP expression profile during normal myeloid differentiation, it is apparent that dysregulation of this axis will contribute to leukemic transformation and maintenance. Recent reports showed that dysregulation of the PTGR networks on RBP genes contributes to oncogenesis in leukemia (9, 11). To understand the RBP gene expression landscape during leukemic transformation, we performed both gene-gene correlation and DGE analysis in the context of normal myelopoiesis and compared HSCs with LSCs and leukemic blast cells.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al has reported cancer-type-specific driver mutations and SCNAs in RBPs (5). Mutations in various RBPs splicing factors such as SRSF2, SF3B1 and U2AF1 have been reported to contribute to myelodysplasia, AML and other blood-related disorders owing to altered binding capacity and dysregulated splicing events (69). Mutations in the ribosomal RBP, RPS14, contribute to myelodysplasia owing to defective 18S rRNA processing (10).…”
Section: Introductionmentioning
confidence: 99%
“…hile extensive research has revealed the crucial importance of transcriptional regulation, the role for post-transcriptional processes in the function of normal and cancer stem cells remains poorly defined. RNA binding proteins (RBPs) provide control of mRNA metabolism and translation of key regulators that mediate stem cells' self-renewal and cell fate decisions 1,2 . Moreover, mutations and aberrant expression of RBPs have recently been implicated in multiple types of cancer, demonstrating the crucial role for RBPs in tumorigenesis [3][4][5][6][7][8][9] .…”
mentioning
confidence: 99%